Penerapan Media Pembelajaran Elektronik untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran Fikih di MI - Hadi, Solihul (MODELING: Jurnal Program Studi PGMI, 2019)
At this time there are still many learning carried out in Madarasah Ibtidaiyah (MI) fiqh subjects that use conventional methods, namely lectures, where teachers who deliver material students only listen. This makes students feel bored and bored. Responding to this to increase students' learning motivation needs the use of learning media. Learning media have an important role in the learning process of students, the media that is considered appropriate and in accordance with these conditions is to use electronic-based learning media. Electronic media is a tool or media that is used by teachers to assist in the delivery of material to students in the form of electronics, so students will be easier to understand and also the learning atmosphere will be more lively and interesting. Electronic media used for example computers or laptops and LCD projectors